PEDAGOGICAL PREREQUISITES FOR THE IMPLEMENTATION OF A VARIATIVE APPROACH TO DEVELOPING EDUCATION - O. P. Aslonova (American Journals, 2023)
This article will comment on the main trends (positive and negative) that need to be implemented in this area in order to apply variative models of developing education. Also cited are problems to be overcome, analyses of potential opportunities of educational institutions. It is noted that the strategy for applying variational modeling is determined on the basis of the goals, directions of the variational model and the main directions of its introduction into practice.
Keywords: Development, variative, approach, pedagogy, models, individuality.